2022
DOI: 10.1097/bpo.0000000000002091
|View full text |Cite
|
Sign up to set email alerts
|

Hip Pain in Patients With Spinal Muscular Atrophy: Prevalence, Intensity, Interference, and Factors Associated With Moderate to Severe Pain

Abstract: Background: A subset of patients with spinal muscular atrophy (SMA) develop hip pain. We analyzed (1) the characteristics of hip pain in patients with SMA (prevalence, intensity, interference with activities, and responsiveness to treatment) and ( 2) factors (patient, clinical, and radiographic) associated with moderate to severe pain. Methods: We performed a retrospective record review and telephone survey of 104 patients with SMA (77% response rate; 44% female; mean age, 22 ± 13 y) who presented for treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 38 publications
1
14
2
Order By: Relevance
“…Our institution's aggressive multidisciplinary treatment of these medically frail children over the past 2 decades, prior to the widespread use of DMTs, allowed this to be the largest, most homogeneous, nonambulatory SMA cohort to be assessed for hip pain. Previous studies have increased sample sizes by combining patients who had SMA with those with other neuromuscular disorders [22][23][24] or have mixed both ambulatory and nonambulatory patients with SMA 25,26 , which may have confounded their results. Sporer and Smith, who combined ambulatory patients with type-III and nonambulatory patients with type-II SMA (n = 41), reported that 45% of the subjects had radiographic hip pathology and only 2 (5%) reported hip pain at a mean follow-up of 14 years 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our institution's aggressive multidisciplinary treatment of these medically frail children over the past 2 decades, prior to the widespread use of DMTs, allowed this to be the largest, most homogeneous, nonambulatory SMA cohort to be assessed for hip pain. Previous studies have increased sample sizes by combining patients who had SMA with those with other neuromuscular disorders [22][23][24] or have mixed both ambulatory and nonambulatory patients with SMA 25,26 , which may have confounded their results. Sporer and Smith, who combined ambulatory patients with type-III and nonambulatory patients with type-II SMA (n = 41), reported that 45% of the subjects had radiographic hip pathology and only 2 (5%) reported hip pain at a mean follow-up of 14 years 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Sporer and Smith, who combined ambulatory patients with type-III and nonambulatory patients with type-II SMA (n = 41), reported that 45% of the subjects had radiographic hip pathology and only 2 (5%) reported hip pain at a mean follow-up of 14 years 26 . In addition, Xu et al, who also combined ambulatory and nonambulatory patients (n = 104), found that 58% of patients reported hip pain 25 . Given the more functionally uniform (nonambulatory), but medically frail, patients in our study, our mean follow-up of 10.4 years and sample size compare favorably with these studies and are larger and longer than those in other published studies describing hip pain in patients with SMA 14,20,23,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotally, we understand a subset of these populations to still experience painful hip displacement that interferes with daily activities. A recent study demonstrated that hip dislocation, as determined clinically or radiographically, is an independent predictor of moderate-to-severe hip pain in patients with SMA [ 9 ]. In the present case, we illustrate that patients with AFM can similarly experience symptomatic hip dislocation related to their low muscle tone and weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this, some physicians question the value of operative treatment for painless hip displacement in these populations, as patients are privy to perioperative complications while potentially achieving only transient benefits. Yet, it must be noted that pain relief following reconstruction can be substantial and improve quality of life, highlighting the value of such procedures in symptomatic cases refractory to more conservative measures [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of diseasemodifying agent (DMA) treatments, 9 including those targeting SMN2 gene splicing (nusinersen, risdiplam) or replacing the defective SMN1 gene (onasemnogene abeparvovec), improvements in function and life expectancy for all SMA types have renewed interest in the impact of hip displacement on the development of hip pain and arthrosis and whether or not it should be surgically treated. 10,11 Although newer DMAs have improved function and overall health in SMA, their effects on the prevention of hip displacement are unknown. The purpose of this study was to determine risk factors for the development of hip displacement in SMA.…”
Section: Introductionmentioning
confidence: 99%